PMEPA1 Is a Prognostic Biomarker That Correlates With Cell Malignancy and the Tumor Microenvironment in Bladder Cancer - Qiu, Dongxu; Hu, Jian; Hu, Jiao; Yu, Anze; Othmane, Belaydi; He, Tongchen; Ding, Jian; Cheng, Xu; Ren, Wenbiao; Tan, Xiyan; Yu, Qiaoyan; Chen, Jinbo; et al. (Frontiers in Immunology, 2021)
Prostate transmembrane protein androgen induced 1 (PMEPA1) has been reported to promote cancer progression, but the potential role of PMEPA1 in bladder cancer (BLCA) remains elusive. We assess the role of PMEPA1 in BLCA, via the publicly available database and in vitro study. PMEPA1 was identified from 107 differentially expressed genes (DEGs) to have prognostic value. GO, KEGG and GSEA analysis indicated the PMEPA1 was involved in cancer progression and tumor microenvironment (TME). Then bioinformatical analysis in TCGA, GEO, TIMER and TISIDB show a positive correlation with the inflammation, infiltration levels of three tumor-infiltrating immune cells (TAMs, CAFs and MDSCs) and immune/stromal scores in TME. Moreover, in vitro study revealed that PMEPA1 promotes bladder cancer cell malignancy. Immunohistochemistry and survival analysis shed light on PMEPA1 potential to be a novel biomarker in predicting tumor progression and prognosis. At last, we also analyzed the role of PMEPA1 in predicting the molecular subtype and the response to several treatment options in BLCA. We found that PMEPA1 may be a novel potential biomarker to predict the progression, prognosis, and molecular subtype of BLCA.